Experience Bharatnatyam through the Lens of Connected Devices - Vandana Bharadwaj (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The COVID-19 pandemic has compelled the performing arts community to explore virtual platforms as a means of continuing their artistic practices. Bharatanatyam, a classical Indian dance form, has also witnessed a shift towards virtual training and performance. The purpose of this abstract is to share my experience in training and performing Bharatanatyam on a virtual platform and discuss the benefits and drawbacks. Alongside I have made an effort to list down few strategies to mitigate the technological drawback to safeguard Bharatnatyam’s authenticity and cultural heritage.